Yield and quality of winter bread wheat depending on sowing dates and methods: a review of global and domestic experience - Dudka, R.; Onipko, V. (Scientific Progress & Innovations, 2025)
The purpose of this article is to systematize and provide a comparative analysis of modern domestic and foreign scientific studies on the influence of sowing dates and methods on the yield and quality of winter wheat, as well as to identify promising approaches to adapting cultivation technologies under varying agro-climatic conditions. The paper presents a comprehensive review of contemporary domestic and international studies on the influence of sowing dates and methods on the yield and grain quality of winter bread wheat. Literature analysis shows that sowing time is a critical factor that determines the duration of autumn vegetation, tillering capacity, accumulation of reserve substances, and, consequently, the plant’s adaptability to winter conditions. Early sowing generally ensures better root development, a stronger root system, a higher tillering coefficient, and contributes to the formation of heavier grains and improved protein quality. However, excessively early sowing under high-temperature conditions may lead to plant overgrowth, disrupted photoperiodism, and reduced winter hardiness. International studies pay particular attention to regional adaptation of sowing dates, the role of agroclimatic factors, the use of yield forecasting models (including neural networks, satellite monitoring, and NDVI analysis), and meta-analyses summarizing data from dozens of field trials. It has been established that a 10-day delay in sowing can reduce yield by 1.5–2.5 %, and in some cases by up to 48 %, depending on climatic conditions, water availability, and varietal traits. The optimal sowing window generally falls between the third decade of September and early October and should be adjusted based on weather patterns and crop rotation practices. Ukrainian studies emphasize regional specifics within Polissia, Forest-Steppe, and Steppe zones. The effectiveness of strip, narrow-row, and broadcast sowing methods has been noted, as they enhance photosynthetic activity, promote uniform crop density, reduce disease incidence, and optimize soil moisture regimes. Some experiments also highlight the role of the preceding crop and carbohydrate accumulation in tillering nodes as key yield-determining factors. The findings have practical significance for improving winter wheat cultivation technologies, adapting to climate change, increasing agroecosystem resilience, and ensuring consistently high grain quality within intensive agricultural production.